IS URINARY CREATININE ASSOCIATED WITH WASTING IN NEONATES - Ningsih, Sri Widia; Andriani Lubis, Nita; Wirda Hayati, Aslis; Azis, Alkausyari (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: To analyze the correlation between creatinine urine and wasting in neonates. Methods: The study was cross sectional by involving 35 healthy neonates aged 1â€“3 days that were born at Pekanbaru Andini Hospital, Indonesia, on August to September 2014. Body length gauges, digital weighing scale, family socioeconomic questionnaires, pediatrics urine collection bag, and creatinine urine were used to collect the data. We used two indicators (creatinine urine and weight/height [WH]) as a parameter in this study. Pearson correlation (significance p<0.05 and p<0.01) was applied for statistical analysis. Results: There was no wasting neonates, WH z-score (WHZ) >-2 SD. The concentrations of absolute creatinine urine excretion were about 11.1â€“167.2 mmol/day, and creatinine urine excretion related to body weight was about 4.08â€“50.06 mmol/Kg/day. Bivariate analysis obtained that there were negative significant correlation between the absolute creatinine urine (r=âˆ’0.357, p=0.035) and creatinine urine â€“ body weight (r=âˆ’0.482, p=0.003) with WH. Creatinine urine measurement is a sensitive biomarker of renal and total muscle mass that can be used as a child’s growth biomarker. Conclusion: The creatinine urine was associated with wasting in neonates therefore can be used as a growth biomarker.